Effect of Dietary Formic Acid and Lignosulfonate on Pellet Quality - G. E. Nichols; C. R. Stark; A. M. Ogles; C. N. Truelock; N. M. Beckman; T. S. Winowiski; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
Nursery pig diets are pelleted to improve handling characteristics and pig performance. Feeding good quality pellets is important to achieve the maximum improvements in growth performance. Therefore, it is important to determine how feed additives included in nursery pig diets influence pellet quality. The objective of this study was to determine the effect of formic acid and lignosulfonate (LignoTech USA) inclusion in nursery pig diets on pelleting characteristics, pellet quality, and diet pH. The 5 treatments consisted of a control, or the control plus 2 concentrations of added formic acid (0.36% or 0.60%), or the control plus two combinations of 60% formic acid and 40% lignosulfonate (0.60% or 1.0%). Diets were steam conditioned (10 × 55 in, Wenger twin shaft pre-conditioner, Model 150) for approximately 30 s and pelleted on a 1-ton 30-horsepower pellet mill (1012-2 HD Master Model, California Pellet Mill) with a 3/16 × 1 ¼ in pellet die (length:diameter ratio of 6.67). The production rate was set at 1,984 lb/h. Treatments were pelleted at 3 separate time points to provide 3 replicates per treatment. Samples were collected directly after discharging from the pellet mill and cooled in an experimental counterflow cooler. Pellet samples were analyzed for pellet durability index using the Holmen NHP 100 (TekPro Ltd, Norfolk, UK) and standard and modified tumble box methods. Pellet hardness was determined by evaluating the peak amount of force applied before the first signs of fracture. Pellets were crushed perpendicular to their longitudinal axis using a texture analyzer (Model TA-XT2, Stable Micro Systems Godalming, UK). Pellet samples were analyzed for pH via potentiometer and electrodes (AACC Method 02-52.01). Voltage and amperage data was collected via Supco DVCV Logger (Supco, Allenwood, NJ) and used to calculate pellet mill energy consumption (kWh/ton). Data were analyzed using the MIXED procedure in SAS v. 9.4, with pelleting run as the experimental unit. Increasing formic acid in the diet decreased pH (P<0.001) by 0.6 to 0.8 in low formic acid diets and by 1 point in the high formic acid diets. When adding formic acid or lignosulfonate to the diet, no evidence for differences was observed for pellet mill energy consumption, production rate, hot pellet temperature, or pellet durability regardless of testing method or pellet hardness. In conclusion, pellet quality was not influenced by formic acid or lignosulfonate, and as expected pH decreased as the level of formic acid increased.
Keywords: formic acid; lignosulfonate; pellet quality